Analysis of Reading Comprehension Skills of the Folklore of Babad Alas Lo in Indonesian Language Subjects - Sujiono Sujiono (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
The purpose of the study was to analyse the reading comprehension skills of Babas Alas Lo folktales of class X Homeschooling Kusalamitra Gunung Kidul students. The type of research is descriptive quantitative research. Data from the reading comprehension skills test of folktales were analysed through descriptive statistics. The research was conducted at Kusalamitra Homeschooling, Wonosari sub-district, Gunung Kidul district. The research implementation time was from April to July 2024. The population used in this study were all grade X Homeschooling Kusalamitra students totalling 19 students. The data collection technique used was the test technique. The results of the research analysis of reading comprehension skills, focusing on the ability to analyse themes, plot, characters and characterizations, story setting, point of view, language style, and meaning in folklore. reading comprehension skills of folklore Babad Alas Lo in Class X Homeschooling Kusalamitra students in the good category. The average value of students' reading comprehension skills is 80.95. Students who successfully scored the reading comprehension skills of Babad Alas Lo folklore in the range of 86-100 (excellent) were 36.86%. 36.86% of the students who got the reading comprehension skill score of folktales of Babad Alas Lo with the range of 76-85 (good). As many as 26.32% of students got the score of reading comprehension skills of folktales of Babad Alas Lo with the range of 56-74 (fair).